Implementation of the Demonstration Method to Improve Fine Arts Learning Outcomes in Class IX of SMP Negeri 7 Samarinda - Djamaludin, Djamaludin (Educationist: Journal of Educational and Cultural Studies, 2023)
This study aims to determine the implementation of demonstration methods to improve art learning outcomes in the class IX State Junior High School 7 Samarinda, which is held for 1 month. Subjects in this study were students Class IX SMP Negeri 7 Samarinda. The number of students who made the subject of research as many as 41 students. The form of research is classroom action research. The instrument of this research consisted of performance instrument and data collection instrument in the form of observation sheet of teacher activity and student activity. Based on the analysis and interpretation of data can be concluded that the increase in student learning outcomes after implemented learning by using the method of demonstration. As it is understanding of students experienced an increase from before the PTK that is in classical completeness only reaches on 39.02 classical completeness but after implemented in the first cycle by using the demonstration method of meeting 1 increased to 75.61 then the classical completeness again increased in cycle II that is to achieve classical mastery 92.68 % or can be said complete learning with all students are able to achieve the value of KKM.